Comparative efficacy and safety of POLARx versus Arctic front advance pro cryoballoon systems for pulmonary vein isolation in atrial fibrillation: an updated systematic review and meta-analysis - Muhammad Fawad Tahir; Muhammad Fawad Tahir; Muhammad Hamza Shuja; Ramish Hannat; Fabeeha Shaheen; Amna Sayeed; Ayesha Shaukat; Faiza Rajput; Muhammad Ahmed Zahoor; Kinza Hamid; Areeba Khan; Aymen Azan Ahmed; et al. (Frontiers in Cardiovascular Medicine)
BackgroundCryoballoon (CB) ablation is a well-established treatment for atrial fibrillation (AF). The Arctic Front Advance Pro™ (AFA-Pro) system, in use for over a decade, has demonstrated consistent efficacy and safety. Recently, the POLARx™, a novel CB system, has gained attention due to its advanced design and comparable clinical outcomes.MethodsWe conducted a systematic review and meta-analysis of studies comparing AFA-Pro and POLARx in patients undergoing CB ablation for AF. Outcomes included procedural parameters (procedure time, ablation time, fluoroscopy time, balloon nadir temperature) and safety endpoints such as phrenic nerve palsy (PNP) and Stroke rates.ResultsThere were no significant differences between POLARx and AFA in acute PVI success (OR = 0.49, P = 0.24), procedure time (MD = 4.40, P = 0.14), ablation time (SMD = 0.12, P = 0.10), fluoroscopy time (MD = 0.34, P = 0.67), freezing time and stroke rates. POLARx showed a significant advantage in balloon nadir temperature (P < 0.00001) and demonstrated longer time to isolation (TTI) in the RSPV (MD = 5.49, P = 0.05) and RIPV (MD = 4.54, P = 0.04), while TTI was similar for the LSPV and LIPV. However, POLARx was associated with a higher risk of PNP (OR = 1.87, P = 0.007).ConclusionPOLARx demonstrates lower balloon nadir temperature but is associated with a higher risk of phrenic nerve palsy compared to AFA-Pro. These findings provide important insights into the procedural efficiency and safety profiles of these cryoablation systems.Systematic Review Registrationidentifier CRD42024588371.